Norway : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2005)
The report on Norway's Observance of Standards and Codes on the Financial Action Task Force Recommendations for Anti-Money Laundering (AML) and Combating the Financing of Terrorism (CFT) is examined. It describes and analyzes those measures, and provides recommendations on how certain aspects of the system could be strengthened. The AML/CFT priorities have been to increase the effectiveness of measures to detect, prosecute, and confiscate proceeds of crime and to enhance international cooperation as well as competence building.